Complementary use of monochromatic and white‐beam X‐ray micro‐diffraction for the investigation of ancient materials. (1st October 2015) - Dejoie, Catherine; Tamura, Nobumichi; Kunz, Martin; Goudeau, Philippe; Sciau, Philippe
<x xml:space="preserve">Abstract</x> Archaeological artefacts are often heterogeneous materials where several phases coexist in a wide grain size distribution. Most of the time, retrieving structure information at the micrometre scale is of great importance for these materials. Particularly, the organization of different phases at the micrometre scale is closely related to optical or mechanical properties, manufacturing processes, functionalities in ancient times and long‐term conservation. Between classic X‐ray powder diffraction with a millimetre beam and transmission electron microscopy, a gap exists and structure and phase information at the micrometre scale are missing. Using a micrometre‐size synchrotron X‐ray beam, a hybrid approach combining both monochromatic powder micro‐diffraction and Laue single‐crystal micro‐diffraction was deployed to obtain information from nanometre‐ and micrometre‐size phases, respectively. Therefore providing a way to bridge the aforementioned gap, this unique methodology was applied to three different types of ancient materials that all show a strong heterogeneity. In Roman terra sigillata, the specific distribution of nanocrystalline hematite is mainly responsible for the deep‐red tone of the slip, while the distribution of micrometre‐size quartz in ceramic bodies reflects the change of manufacturing process between pre‐sigillata and high‐quality sigillata periods. In the second example, we investigated the modifications occurring in Neolithic and geological flints after a heating process. By separating the diffracted signal coming from the nano‐ and the micrometre scale, we observed a domain size increase for nanocrystalline quartz in geological flints and a relaxation of the residual strain in larger detritic quartz. Finally, through the study of a Roman iron nail, we showed that the carburation process to strengthen the steel was mainly a surface process that formed 10–20 µm size domains of single‐crystal ferrite and nanocrystalline cementite.